الاجهاد الذهني وعلاقته بالذاكرة قصيرة المدى لدى طلبة الجامعة (Journal Of Educational and Psychological Researches, 2015)
Mental stress occurs due to the effect of time that passes at an accelerated pace and doing business imposed by the speed of the match with his speed in light of the vast amount of audio and visual information through scientific progress and media workers, as well as the impact of physical factors associated with doing business, such as noise and congestion .... . etc.. The relationship of the individual to take a negative surroundings have devastating effects on the cognitive process as a whole dimension. This creates a sense of helplessness with the depletion voltage to a state of mental stress, so The problems from the standpoint of Aljhtalt scientists are basically cognitive problems appear to exist when it happens to the individual tension or stress as a result of the interaction between cognition and thinking in order to solve a problem, and so mental stress works to secretion cortisol harmful cortisol, and cause of this article series of reactions in the body, including the weakening of the immune system, and tension in the large muscles, high blood pressure, and repeat the high proportion of cortisol, which leads to the death of brain cells, especially in the so-called hippocampus hippocampus region which is necessary for the memory area Accordingly, current research aimed to identify the following:1-measure the level of mental stress (according to test the flicker fusion frequency) among university students.2-measuring short-term memory level (according to test accuracy) with university students.3-finding the relationship between mental stress and short-term memory with university students.Identifies research to current students of the University of Baghdad (Jadiriya complex) for the academic year 2012-2013 scientific and humanitarian disciplines of males and females.In light of the objectives of the research and after the application of the two tools Search Aided and using appropriate statistical methods was reached the following results:1-There is no morally significant differences between males and females in the level of mental stress on the merger in accordance with the frequency variable, meaning that males and females Atzmon same mental stress. afternoon that there is a difference in recall between males and females, and in favor of females. There is a direct correlation statistically significant between mental stress and short-term memory, and can interpret this result as increased mental stress whenever weakness remembering.In light of these findings the researcher presented a number of recommendations and suggestions.